Metabolomics Analysis of the Renal Cortex in Rats With Acute Kidney Injury Induced by Sepsis - Ping, Feng; Guo, Yong; Cao, Yongmei; Shang, Jiawei; Yao, Sijia; Zhang, Junfeng; Li, Yingchuan (Frontiers in Molecular Biosciences, 2019)
Sepsis-induced acute kidney injury (AKI) can increase the mortality of critically ill patients and the incidence of chronic kidney disease in critically ill survivors. The main goal was to investigate the possible link between metabolic changes and sepsis-induced AKI development. The experimental animal model of sepsis-induced AKI was established by intraperitoneal injection of lipopolysaccharide in rats. Nontargeted metabolic screening of the renal cortex in the control and sepsis-induced AKI groups was carried out based on gas chromatography coupled with quadrupole time-of-flight mass spectrometry (GC-TOFMS) technology. The data between the two groups were analyzed by combining univariate and multivariate statistical methods, and the metabolites associated with AKI in rats with sepsis were screened. By examining the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, altered metabolic pathways associated with acute renal injury in sepsis were identified. The cross validated scores plot of orthogonal partial least squares discriminant analysis (OPLS-DA) showed a distinct separation trend between the model and control groups in the profile of renal cortex metabolites, indicating a significant change in endogenous metabolites in the rat renal cortex. Further analysis and screening showed that 26 different metabolites were identified in the renal cortex between the two groups, mainly involving taurine and hypotaurine metabolism, pantothenic acid and CoA biosynthesis, phenylalanine metabolism and other metabolic pathways. The metabolic disorders of taurine, pantothenic acid and phenylalanine in the renal cortex are related to the development of acute renal injury in sepsis. Correcting these metabolic disorders is expected to prevent and treat sepsis-induced AKI.